Meningkatkan Kreativitas Mahasiswa Melalui Pemanfaatan Kerang Laut Sebagai Hiasan Kaca - Maya Goram Gaman; Chintana E.I Siahaya; Dhestella Aronggear; Maichy C. Peo; Susana Magdalena Welly Muskita (Jurnal Manajemen Kewirausahaan dan Teknologi, 2024)
In this era of development, there are many things that young people, especially students, can do to produce creativity from various types of unused materials and manage them into quality and valuable creativity. The aim of the creativity program for managing sea shells as glass decorations is useful creativity which can help students create creativity with very minimal capital and sell it at varying and profitable prices for students. This creativity also helps students' economy to meet their personal and college needs. The use of sea shells as glass decorations is a motivation for students who want to get involved directly in the world of entrepreneurship with minimal capital, materials that are environmentally friendly and very easy to obtain.